Mystery map - Dixon, Franklin W.; Burroughs, Scott (New York, NY : Scholastic., 2010)
On their way through the park, Frank and Joe find a mysterious map that looks like it leads to treasure, but the brothers must face bullies hanging around where the map leads.
H
b
b